Use of eye level height to determine signage height in public hospital - Basri @ Boseri, Ahmad Qadri; Sulaiman, Ruhaizin (Faculty of Design & Architecture, Universiti Putra Malaysia, 2017)
Signage provides information and direction. It is important as a medium to show direction in offices and public buildings. Simply implementing signage within facilities, such as hospitals, does not necessarily improve people’s way finding experience. Incomplete information and confusion of signage are among common issues being raised by the public to hospital management. This study is carried out to determine user height preferences of Kajang Hospital’s signage and to propose an appropriate height for its future signage. 400 respondents participated in this study. They are aged between 18 to 60 years old with the mean of age at 39 years old. Their stature height and eye-level height are measured using SECA Stable Stadiometer. A set of questionnaire is distributed to measure their preferences towards the present signage. The studied signage is also measured using standard measuring tape. The data is analyzed using SPSS. The difference height of the existing signage at the hospital compared to the distribution graph was 68.50 cm (below than 5th percentile), while 115.50 cm (higher than 95th percentile). Suggested range of signage height for Kajang Hospital is 68 cm to 165 cm. The present signage requires necessary height readjustment to be more appropriate for the majority of the users.